Investigation of advanced temperature and thermo shock resistant ceramic components for high temperature porous burners - Jovicic, Vojislav; Zbogar-Rasic, Ana; Kempe, Viktor; Delgado, Antonio; Weiß, Roland; Dannehl, Manfred; Pritzkow, Walter E. C.; Grenz, Reinhard (Proceedings of the 10th European conference on industrial furnace and boilers, 2015)
Expansion of operation range toward higher temperatures is one of the major goals in further development of porous burner technology. This is mostly related to the fact that radiation is the most intensive mechanism of heat transfer from a porous burner to a heated object. Therefore, increase of average temperature generally leads toward higher overall efficiency. In addition, higher average temperatures are opening new possibilities for industrial application of low pollutant porous burner technology. In this study, a series of novel high-performance ceramics in various designs were investigated in short and continuous long-term experiments under different controlled combustion conditions. Materials like fiber-reinforced alumina ceramics, paper-based pre-ceramic materials and wood-based bio-ceramics were successfully characterized. Long-term combustion tests with test time of 100-500 test hours of continuous operation per test, were conducted at near stoichiometric combustion conditions using mixture of natural gas and air. Most of the tested structures and materials was for the first time tested as a porous burner component at this temperature range within the frame of here presented work. Presented results provide significant amount of useful data regarding performances and limitations of investigated novel ceramic materials and structures and also their potential for application as high temperature (1500°C and above) and thermal shock resistant porous burner components like combustion zones, flame traps or burner housing
UnivIS-Import:2017-07-10:Pub.2015.tech.ITC.stmmec.invest